An auto-scoring mechanism for evaluating problem-solving ability in a web-based learning environment - Chiou, Chuang-Kai; Hwang, Gwo-Jen; Tseng, Judy C.R. (Computers and education, 2009)
The rapid development of computer and network technologies has attracted researchers to investigate strategies for and the effects of applying information technologies in learning activities; simultaneously, learning environments have been developed to record the learning portfolios of students seeking web information for problem-solving. Although previous research has demonstrated the benefits of applying information technologies to learning activities, the difficulties in doing so have also been revealed. One of the major difficulties is the lack of a mechanism to assist teachers in evaluating the problem-solving ability of the students, such that constructive suggestions can be given to the students, and tutoring strategies can be improved accordingly. To cope with this problem, in this paper, an auto-scoring mechanism is developed to analyze the various information searching abilities of individual students. Indicators of information searching ability (ISA) are proposed based on the famous Big6 model and are adopted in our auto-scoring mechanism. Moreover, two experiments have been conducted to demonstrate the effectiveness of this innovative approach. The experimental results show high correlation between the scores of the auto-scoring mechanism and the manual scoring. Moreover, the feedbacks from 158 teachers also show that the innovative approach is highly accepted by the teachers.